Business analytics competencies in stabilizing firms’ agility and digital innovation amid COVID-19 - Cai Li; Adnan Khan; Hassan Ahmad; Mohsin Shahzad (Journal of Innovation & Knowledge, 2022)
Digital innovation is not a technology in itself but businesses’ ability to exploit digital technology to resolve outmoded problems. Digital innovation is leveraging improvements or innovating technology to reimagine business practice. The Coronavirus disease 2019 exerted enormous effects on people's physical and psychological health. In addition, this pandemic adversely affected the global economy, from sole proprietors to multinational firms. However, such an effect did not hinder versatile products, services, and upgraded versions of technologies. Modern firms rely heavily on available data sets to make decisions through analytics. Manufacturing is one of the most dynamic industries due to market pressures and continually changing customer demands. This study examines the relationship between business analytics competencies and digital innovation and explores the mediating role of absorptive capacity and firm agility. Data are collected from 493 managers of manufacturing firms and analyzed by using structural equation modeling through smart-PLS. Results reveal a positive relationship between business analytics competence and digital innovation mediated by absorptive capacity and firm agility. With its theoretical contributions, this study can initiate practical research outcomes in manufacturing firms.